1996
DOI: 10.1159/000201355
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Motilin Release from Isolated Perfused Pig Duodenum

Abstract: The release of motilin from an isolated preparation of pig duodenum has been studied. Three different types of stimuli were applied: electrical nerve stimulation, intraarterially administered peptides, and instillation of test solutions into the lumen of the duodenum. Furthermore, extracts of 20 different regions of the pig digestive system have been analyzed for motilin content. Analysis of the extracts only detected significant presence of motilin in the pig duodenum and jejunum (79 ± 15 and 60 ± 19 pmol/g).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Woodtli and Owyang ( 114 ) found that duodenal pH changed from 2 to 7.5 during the onset of phase I to phase III, and that pH was maintained at alkaline from late phase II to phase III of the gastric MMC. Acidification-induced motilin release was also observed in the isolated perfused pig duodenum ( 101 ). These studies have indicated that both duodenal acidification and alkalinization stimulate motilin release and induce GI contraction like phase III ( Table 2 ).…”
Section: Regulation Of Motilin Releasementioning
confidence: 90%
“…Woodtli and Owyang ( 114 ) found that duodenal pH changed from 2 to 7.5 during the onset of phase I to phase III, and that pH was maintained at alkaline from late phase II to phase III of the gastric MMC. Acidification-induced motilin release was also observed in the isolated perfused pig duodenum ( 101 ). These studies have indicated that both duodenal acidification and alkalinization stimulate motilin release and induce GI contraction like phase III ( Table 2 ).…”
Section: Regulation Of Motilin Releasementioning
confidence: 90%
“…[7][8][9] Subsequent studies demonstrated that a variety of alterations in GI luminal conditions, including acidity, pressure and increased nutrient concentration, induce intestinal mucosa to release 5-HT. [10][11][12][13] While other neuroactive compounds, such as cholecystekinin (CCK) and motilin, are released by luminal stimulation, 14,15 it is 5-HT that seems to play a particularly critical role in sensory perception, secretion and peristalsis. The 5-HT released from EC cells is important because it represents the earliest intercellular event in the transduction of mucosal stimuli that initiates the neuronal reactions responsible for visceral sensation and peristalsis.…”
Section: Serotonin Signalling and Function Within The Gutmentioning
confidence: 99%
“…45,46 It is quite possible that several mechanisms are responsible and that motilin release is dependent on the equilibrium between stimulating and inhibiting factors. 47 …”
Section: Gi Activity Among Humans and Motilinmentioning
confidence: 99%